UPAYA KULTURAL SEKOLAH DALAM MEMPERCEPAT PENCAPAIAN VISI DAN MISI PADA SEKOLAH DASAR INTEGRAL - Mugni Labib (Program Studi Manajemen Pendidikan Islam, 2023)
Discusses school culture to show how the school's vision and mission aim to accelerate the achievement of the school's vision and mission at Madrasah Ibtida'iyah Darul Ulum. This study is a qualitative field study with data collection techniques, namely observation, interviews, and documentation. Data analysis in this study uses descriptive analysis techniques, which involve analysing data in the form of words, images, and not numbers. The results of this study, in line with the research questions, can be summarised as follows: The school culture at MI Darul Ulum includes: a. Greeting culture, b. Rituals, such as collective prayer, congregational Zuhr prayer at the beginning of the time, congregational Dhuha prayer, and chanting slogans, c. Celebrations and traditions, such as Monday ceremonies, motivational assemblies, and sixth-grade graduation ceremonies, as well as student creativity events, d. Routines, such as advice sessions, orientation programmes, clean-up Saturdays, self-defence training, writing reflection journals and communication journals, Ramadan camps, and memorising Quran chapters 30 and 29. 2) The role of school cultural efforts is highly significant as a contributor to accelerating the achievement of the school's vision and mission at Madrasah Ibtida’iyah Darul Ulum